THE EFFECT OF DISCIPLINE AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE AT PT. MANDIRI UTAMA FINANCE DUREN TIGA BRANCH WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Ilham Syahbana Limbong; Cecep Haryoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study uses job satisfaction as a mediating variable to evaluate how work competence and discipline affect employee performance at PT. Mandiri Utama Finance, Duren Tiga Branch. 150 workers completed a survey utilizing questionnaires, and the results were examined using Smart PLS's Structural Equation Modeling (SEM) tool. The findings demonstrate that competence and discipline have a considerable influence on employee performance (coefficients of 0.146 and 0.192, respectively) and work satisfaction (coefficients of 0.412 and 0.356, respectively). Performance is significantly impacted by job satisfaction as well (coefficient of 0.503). Additionally, via job satisfaction, competence and discipline have a considerable influence on employee performance (coefficients of 0.490 and 0.479, respectively).